Protective effects of butyrate on cerebral ischaemic injury in animal models: a systematic review and meta-analysis - Yan, Shichang; Ji, Qipei; Ding, Jilin; Liu, Zhixiang; Wei, Wei; Li, Huaqiang; Li, Luojie; Ma, Chuan; Liao, Defu; He, Ziyan; Ai, Shuangchun (Frontiers in Neuroscience, 2024)
Cerebral ischemic stroke is a common disease that poses a serious threat to human health. Butyrate is an important metabolite of intestinal microorganisms. Recent studies have shown that butyrate has a significant protective effect in animal models of cerebral ischemic injury. Objective of this study: To evaluate the protective effect of butyrate on cerebral ischemic stroke by meta-analysis, aiming to provide a scientific basis for the clinical application of butyrate in patients with cerebral ischemia. Materials and methods: A systematic search was conducted for all relevant studies published before January 23, 2024, in PubMed, Web of Science, Cochrane Library, and Embase. Methodological quality was assessed using Syrcle's risk of bias tool for animal studies. Data were analysed using Rev Man 5.3 software. Results: A total of nine studies were included and compared with controls, butyrate significantly increased BDNF levels in the brain (SMD = 2.33, 95%CI = [1.20, 3.47], P < 0.005). and P-Akt expression (SMD = 3.53 95%CI = [0.97, 6.10], P < 0.05). Butyrate also decreased IL-β levels in the brain (SMD = -2.02, 95%CI = [-3.22, -0.81], P < 0.005), TNF-α levels (SMD = -0.86, 95%CI = [-1.60, -0.12], P < 0.05), and peripheral vascular IL-1β levels (SMD = -2.10, 95%CI = [-3.59, -0.61], P < 0.05). In addition, butyrate reduced cerebral infarct volume (MD = -11.29, 95%CI = [-17.03, -5.54], P < 0.05), mNSS score (MD = -2.86, 95%CI = [-4.12, -1.60], P < 0.005), and Foot fault score 35], P < 0.005), and Morris water maze time (SMD = -2.49, 95%CI = [-4.42, -0.55], P < 0.05). CONCLUSION: The results of this study indicate that butyrate has a protective effect on cerebral ischemic stroke in animal models, and the mechanism is related to reducing inflammation and inhibiting apoptosis. It provides an evidence-based basis for the future clinical development of butyrate in the treatment of ischemic stroke.